2013
DOI: 10.4236/as.2013.47045
|View full text |Cite
|
Sign up to set email alerts
|

Soybean meal as a source of protein in formulated diets for tiger grouper, <i>Epinephelus fuscoguttatus</i> juvenile. Part I: Effects on growth, survival, feed utilization and body compositions

Abstract: The effects of fish meal (FM) replacement with graded level of soybean meal (SBM) on growth performance, feed utilization, survival rate and body composition were investigated in juvenile tiger grouper, Epinephelus fuscoguttatus (initial body weight 13.9 ± 0.65 g). Six experimental diets were formulated to contain 50% crude protein, 16% crude lipid and 365.8 kcal/100g feed with SBM replacing FM protein at 0% (SM 0), 10% (SM 0), 20% (SM 20), 30% (SM 30), 40% (SM 40) and 20% with phytase (SM 20P) replacement lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 32 publications
5
24
2
Order By: Relevance
“…However, no significant difference ( p > .05) was observed between fish fed with 0% and 30% of DSM. This observation was similar to the parental fish brown‐marbled grouper juvenile which only can tolerate 20% to 30% of DSM (Shapawi, Ebi & Yong, ). In a study that replaced fish meal with FSM and DSM in the feed for brown‐marbled grouper, Chor et al.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, no significant difference ( p > .05) was observed between fish fed with 0% and 30% of DSM. This observation was similar to the parental fish brown‐marbled grouper juvenile which only can tolerate 20% to 30% of DSM (Shapawi, Ebi & Yong, ). In a study that replaced fish meal with FSM and DSM in the feed for brown‐marbled grouper, Chor et al.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, this hybrid grouper has great potential to expand in aquaculture industry. Parent fish, brown‐marbled grouper was found be able to accept 20%–30% of DSM (Shapawi, Ebi & Yong, ; Shapawi, Ebi, Yong, Chong et al., ). On the other hand, replacement of fish meal with FSM did not improved growth of this species due to its palatability issue (Chor et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The fishmeal and defatted soybean meal used in this present study were of the same sources with those used in tiger grouper study by Shapawi et al (2013a) and the study reported that a deficiency of essential methionine amino acid was found in higher soybean meal-based diet compared to the control diet. Although amino acid analysis was not performed in this present study, with reference to Shapawi et al (2013a), it is suggested that the diet contained high level of soybean meal SB20 and SB20+P contained less methionine amino acid compared to SB10. These could have contributed to the slower growth in marble goby juveniles fed higher level of soybean meal.…”
Section: Discussionmentioning
confidence: 95%
“…The acceptance level of soybean meal by the marble goby juveniles in present study however, is lower compared to other bigger size of carnivorous fish reported elsewhere. Shapawi et al (2013a) demonstrated that tiger grouper juvenile (Epinephelus fuscoguttatus) of initial BW 13.9 g can accept 20-30% of defatted soybean meal protein without adversely affected their growth and feed utilization. Black sea turbot (Psetta maeotica) with an initial BW of 30.2 g can utilize up to 20% of defatted soybean meal with the supplementation of attractant (Yigit et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation